Post-intubation laryngotracheal stenosis: clinical presentation and management approaches - Jihene Houas; Monia Ghammam; Heyfa Belhadj-Miled; Mouna Bellakhdher; Malika El Omri; Meherzi Abir; Kermani Wassim; Mohamed Abdelkefi (The Egyptian Journal of Otolaryngology, 2023)
Abstract Introduction Addressing acquired laryngotracheal stenosis presents a complex healthcare dilemma. Results We present a case series of 48 acquired post-intubation laryngotracheal stenosis cases managed within our Department of ENT Surgery at Farhat Hached Tunisia. Diagnosis relied on imaging and endoscopic findings. Among these cases, 28 exhibited tracheal stenosis, with 60% falling into grade 2–3 severity. Management approaches included sole endoscopic dilation for 17 patients, surgical intervention for 19 patients, and T-tube placement for 10 patients. Conclusions The management of laryngotracheal stenosis poses a challenge for ENT surgeons. Prevention is paramount, encompassing various measures such as employing high-volume, high tracheostomy, and extended intubation practices.